Prioritas Perbaikan Layanan Ruang Tunggu Penumpang Bus Trans Kota Batam - Adi Nugroho (Institut Transportasi dan Logistik Trisakti, 2019)
This study aims to determine the priority of improving trans bus public transportation services in Batam City. Research focuses on passenger waiting room facilities which are one of the highlights of the local community because they are directly related to the security and comfort aspects of service users. This research method uses a quantitative descriptive approach by combining it with the importance-performance analysis (IPA) method to group attributes based on the perspective of service users. From the results of measurements that have been made, information on facilities that need to be the top priority for improvement includes the addition of lighting in the waiting room of the bus corridor, the availability of special space for service users who use wheelchairs, seats intended for persons with disabilities and the elderly, children - children and pregnant women, special stairs for service users who use wheelchairs, trash bins available in the waiting room of the bus corridor and increase the number of seats in the waiting room of the bus corridor. This statement is a factor that is considered important by service users but has not been met by the trans city bus service provider Batam